Imperforate hymen with hematocolpos. A case report - González Monzón, Briselda (2023)
Imperforate hymen is a rare congenital malformation recognized as the mostcommon cause of hematocolpos. Most patients with imperforate hymen areunderdiagnosed until the manifestation of obstructive symptoms in adolescence.We present the case of a 13-year-old female diagnosed with imperforate hymen withhematocolpos.